Information for rural development: the ACP states identify their priorities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
As a direct consequence of political and economic liberalization, information and communication have become resources ofprimary importance within the economic sector and an essential element of any business enterprise. Policy makers have asimilar...